Measuring permanent responses to capital-gains tax changes in panel data - Burman, Leonard E.; Randolphs, William C. (American Economic Review, 1994)
The authors use panel data and information about differences in state tax rates to separate the effects of transitory and permanent tax rate changes on capital-gains realizations behavior. The estimated effect of permanent change is substantially smaller than the effect of transitory change. The difference is even larger than differences between estimates from past micro data studies, which have primarily measured the transitory effect, and time-series studies, which have primarily measured the permanent effect. The authors' results resolve a long-standing conflict between micro data and time-series studies of how marginal tax rates affect capital-gains realizations behavior. Copyright 1994 by American Economic Association.